An empirical evaluation of enhanced teleportation for navigating large urban immersive virtual environments - Shahbaz Badr, Arash; De Amicis, Raffaele (Frontiers in Virtual Reality, 2023)
Navigation is the most prevalent interaction in large urban virtual environments (VEs). Any Metaverse application that foresees navigating or exploring virtual cities requires an effective and efficient navigation technique. These environments, however, have distinct characteristics that make the navigation more challenging and the design of the interactions more critical. We have conducted an empirical study to assess how enhancing the teleportation technique with additional capabilities affects the performance of navigating large urban VEs. For this purpose, three interactions have been developed that extend the conventional point-and-click teleportation. The first one is named Mini-Map and provides a top-down view of the user’s surroundings. Portal Preview provides a preview of the selected target location and allows users to choose their desired orientation at that location. The last technique, called X-Ray Vision, makes the buildings around the user translucent and allows teleporting to locations that would otherwise be obscured. A within-subject controlled lab study with twenty five participants has been conducted, where each extension is evaluated individually as well as in combination with others. Our results show that extending the teleportation can significantly improve its performance when navigating large urban VEs. Overall, the X-Ray Vision was the most successful extension with respect to both task metrics and usability measures. Mini-Map was able to improve some of the task metrics, but did not have a significant effect on most self-reported measures. Portal Preview was the least effective extension, however, multiple participants liked the fact that they could define their desired orientation with the controller. Combining all interactions together performed well with respect to the task metrics, but this option was not favored by the participants. Extending the teleportation with X-Ray Vision and Mini-Map was by far the most favored option.